Sustainable Building Improving Environmental, Social and Economic Performance for Tropical Climate - Masoud Esfandiari; Suzaini Mohamed Zaid; Nur Farhana Azmi (Penerbit UTHM, 2023)
Sustainable Building: Improving Environmental, Social, and Economic Performance for Tropical Climate is a comprehensive book that delves into the essential aspects of creating sustainable and healthy indoor environments for nonresidential buildings, with a specific focus on tropical climates. It serves as a valuable resource for students, academics, designers, and stakeholders in the building sector, providing insights and guidance for enhancing building designs and achieving improved indoor conditions. The book covers a wide range of topics, with a particular emphasis on indoor environmental quality (IEQ) parameters and their impact on occupant comfort, health, wellbeing, performance, and productivity. By addressing these factors, the authors aim to contribute to the development of sustainable, green, and healthy built environments, paving the way for a brighter future.